A case of multiple cutaneous lesions due to Serratia marcescens in an immunocompromised patient. Issue 3 (June 2015) - Ray, Ujjwayini; Dutta, Soma; Chakravarty, Chandrashish; Sutradhar, Arpita
Abstract : Introduction: Serratia marcescens is an opportunistic Gram-negative bacillus capable of causing serious nosocomial infection. Skin infections due to S. marcescens, although not frequently encountered, can have a variety of manifestations and may progress to become serious debilitating lesions if not diagnosed early and treated promptly. We report here a case of multiple skin lesions due to S. marcescens in an immunocompromised patient. Case presentation: A 60-year-old patient on adjuvant chemotherapy for breast carcinoma developed a high fever followed by multiple painful nodular and ulcerated lesions over all four limbs. Multidrug-resistant S. marcescens was isolated from the blood as well as from several skin lesions. Removal of the infective source (a chemoport in this case) and administration of tigecycline resulted in resolution of the infection. Conclusion: S. marcescens is a nosocomial pathogen capable of causing extensive cutaneous lesions. Multiple samples for culture from the lesions are recommended to identify the aetiological agent and institute appropriate antibiotics. The emergence of multidrug-resistant strains has compromised treatment options for this bacterium, which is intrinsically resistant to several groups of antibiotics.